Forage grasses in the U.S. Virgin Islands - Oakes, A.J. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Native and exotic warm-season grasses, including corn and sorghum, were evaluated in field trials as crops for fresh forage and silage. The evaluation includes an estimate of mode of spread and ease of establishment, reproductive capacity, rapidity of ground cover and recovery rate, regrowth capacity, competitive ability, stand maintenance, yield, and drought and pest tolerance.